'How' we do social work, not 'what' we do. Issue 2 (4th May 2017) - Røysum, Anita
Abstract: This article explores how Norwegian social workers at municipal social services offices experience and explain social work as professional knowledge and theory, and examines examples from their experience working in new, multi-professional settings. It draws on a qualitative multi-method study focused on professional knowledge in social work practice during and after the reform merging state offices for employment, social insurance and components of municipal social services into 'one-stop shops' – called Nav offices. The study found social workers articulating their professional ethical perspectives as social work while defining themselves as 'us' distinct from their new colleagues. Paradoxically, they found themselves facing challenges in articulating social work theoretically. Their focus was not necessarily on what they did as social workers – but on how they did it. In de-emphasizing the theoretical in favour of the principles and practical benefits of their profession, they took on roles of pragmatic and non-protectionist professionals. They became pragmatic in their efforts to safeguard the best interests of clients while being nonprotective of their professional knowledge in claiming everyone can practice social work if what one does is 'good'. One possible consequence of this is that the expert knowledge involved in social work may become degraded to ordinary and everyday knowledge.